Actividad antibacteriana in vitro de los extractos de corteza y hoja de swartzia polyphylla d.c (cumaceba) por método de sensibilidad - Saldaña Casternoque, Gilmar (2024)
The aim of the research was to determine in vitro the antibacterial activity of petroleum ether and ethanolic extracts of the bark and leaf of Swartzia polyphylla D.C. (cumaceba). The research was experimental, with quantitative approach, Swartzia polyphylla D.C. bark and leaf were used as plant sample, the extract was obtained by maceration, then qualitative phytochemical screening was carried out. Antimicrobial activity was developed following the "Kirby Bauer" disc diffusion methodology, gentamicin and ciprofloxacin discs were used as positive controls. The results show that the petroleum ether extract of leaf and bark did not show any inhibitory activity and the microorganisms tested were resistant. The ethanolic extract of leaf and bark, against the microorganisms Enterococcus hirae, and Staphylococcus aureus, showed sensitive and intermediate activity, with inhibition halos in ranges from 13,0±0,0 mm to 14,7±0,1 mm, Escherichia coli, Enterococcus faecalis, and Salmonella typhimurium, showed resistance to the tested extracts with inhibition ranges from 9,0±0,1 mm to 11,0±0,1 mm. The study concludes that the petroleum ether extract did not show inhibitory activity, while the ethanolic extract of leaf and bark showed antibacterial activity, and this is possible due to the presence of quinones, flavonoids, phenols, coumarins, catechins and terpenes present in the composition of these extracts.